Bioatividade dos cimentos de ionômero de vidro: analise em MEV/EDS, FTIR/ATR, DRX, atividade antimicrobiana e citotoxicidade. - OLIVEIRA, Thais Thais Bezerra da MacenoBezerra da Maceno (2022)
Objective: to evaluate the release of F-, Ca+2, PO4-3 ions, alkalinizing activity, cytotoxicity, antibacterial activity and the capacity to induce the formation of mineral precipitates precursors of hydroxyapatite of glass ionomer cements (GIC). Materials and Methods: Six comercial GICs were evaluated: Bioglass (Biodinâmica), Goldlabel (GC), Vitrofil (DFL), Maxxion (FGM), Vidrion (SS WHITE) and Ionglass (Maquira). Disks were made (n=4) for pH and ionic release tests, which were stored in 6 ml of deionized/distilled water with initial pH (pHi) 4 and 7 for 28 days at 37oC. ph readings were taken at different times (15min, 30min; 1,2, 24 and 48 h; 7,14, 21 and 28 days). After 28 days, the release of F- was analyzed using a specific electrode and the release of Ca+2 and PO4-3 were measured in a UV light spectrophotometer (BioTek ELX800). Fibroblastic cells were used for cytotoxicity, samples were immersed (n=3) and analyzed at 24, 48 and 72hrs. For the analysis of the capacity to induce the formation of hydroxyapatite nano precursors, disks were made (n = 2) and stored in simulated body fluid (SBF) for 28 days at 37ºC. After immersion, specimens were dissected and analyzed in Scanning Electron Microscopy (SEM/EDS), Fourier Transform Infrared Spectroscopy (FTIR/ATR) and X-Ray Diffraction (XRD). S. mutans biofilms were cultured over GIC disks (n=3) to verify their antibacterial activity, which were determined by counting of colony unit formations and expressed as CFU/ml. The data of ionic release, cytotoxicity and antibacterial activity were submitted to ANOVA (One-Way) and Holm-Sidak (α=0,05). Data referring to pH are represented in descriptive values. Results: Regardless of pHi, all GIC were acidic over 28 days. Bioglass showed greater fluoride release when compared to Gold Label (p<0,05), at pH 4. At pH 7, there was no difference on F- release between tested materials. Ionglass and Vitro fill had the highest release of Ca+2 and PO4-3, respectively. SEM images indicated the presence of precipitates on the surface of all GICs and FTIR spectra showed the presence carbonate (1080/1413/1453 cm-1) functional groups. Meanwhile, XRD analyzess did not indicate cristalline peaks of hydroxiapatite nano precursors in any of the glass ionomer cements tested. Regarding cell viability, all GICs presented cytotoxicity when compared to the control group in 72h (p<0,05). The GICs tested did not show antibacterial activity against S. mutans (p<0,05). Conclusion: GICs present important ion release for remineralization. However, their low pH, cytotoxicity, absence of antibacterial activity and the non-formation of hydroxyapatite precursors precipitates indicate that